Translation studies - Kunz, Kerstin; Teich, Elke (The Routledge handbook of systemic functional linguistics, 2017)
This chapter provides an overview of (a) how translatology has harnessed SFL as a - framework for theorising and modelling translation, and (b) the various ways in which SFL - has engaged in translation research. In the next section, it provides a brief history of SFL’s - involvement in translation studies, mainly discussing Catford’s seminal work and Halliday’s - expositions on translation. It goes on to look at SFL’s notion of register as a suitable basis for - theorising and modelling translation. The chapter then discusses recent research on translation applying SFL for different research objectives such as register variation and regarding - grammatical metaphor, cohesion and appraisal. A brief overview of the methods employed - in the analysis of translation(s) follows and then we briefly describe the current practices in - SFL-based translation research, with a focus on corpus-based studies. Finally, we briefly - sketch possible future directions in SFL-based translation research.